D6 blastocyst transfer on day 6 in frozen-thawed cycles should be avoided: a retrospective cohort study - Huiling Xu; Shumin Qiu; Xiaojing Chen; Suqin Zhu; Yan Sun; Beihong Zheng (BMC, 2020)
Abstract Background There is no definitive evidence about the suitable timing to transfer blastocysts formed and cryopreserved on day 6 (D6 blastocysts) in frozen-thawed embryo transfer (FET) cycles. This study aimed to investigate the suitable timing to transfer D6 blastocysts in FET cycles and to identify factors affecting clinical pregnancy rate (CPR) and early miscarriage rate (EMR) in FET cycles with blastocysts. Methods This retrospective cohort study included 1788 FET cycles with blastocysts. There were 518 cycles with D6 blastocysts, and 1270 cycles with blastocysts formed and cryopreserved on day 5 (D5 blastocysts) (D5 group). According to the blastocyst transfer timing, the cycles with D6 blastocysts were divided into cycles with D6 blastocysts transferred on day 5 (D6-on-D5 group, 103 cycles) and cycles with D6 blastocysts transferred on day 6 (D6-on-D6 group, 415 cycles). The chi-square test, independent t-test or Mann-Whitney test, and logistic regression analysis were used for data analysis. Results The CPR and implantation rate (IR) were significantly higher in the D6-on-D5 group than in the D6-on-D6 group (55.3% vs. 37.3%, 44.8% vs. 32.6%, P < 0.01). The CPR and IR were significantly higher in the D5 group than in the D6-on-D5 group (66.0% vs. 55.3%, 62.1% vs. 44.8%, P < 0.05), and the EMR was significantly lower in the D5 group than in the D6-on-D5 group (11.2% vs. 21.1%, P < 0.05). Logistic regression analysis demonstrated that transfer D6 blastocysts on day 5, instead of day 6, could significantly increase the CPR (odds ratio[OR]: 2.031, 95% confidence interval (CI): 1.296-3.182, P = 0.002). FET cycles with D6 blastocysts transferred on day 5 had a higher EMR than those with D5 blastocysts (OR: 2.165, 95% CI: 1.040-4.506, P = 0.039). Hormone replacement therapy (HRT) cycles exhibited a higher EMR than natural cycles (OR: 1.953, 95% CI: 1.254-3.043, P = 0.003), while no difference was observed in the CPR (P > 0.05). Conclusions These results indicate that the suitable timing to transfer D6 blastocysts in FET cycles may be day 5, and D6 blastocyst transfer on day 6 in FET cycles should be avoided. D6 blastocysts transfer and HRT cycles may be associated with a higher EMR.